Patologias em processos de reequilíbrio econômico-financeiro de concessões: prevenção e reparação - Sartal, Estevam Palazzi (2017)
The aim of this study was to grant stability during the execution of concessions contracts, specifically at economic and financial balance adjustments processes. To achieve this objective, it was identified the most frequent disobediences by public administration at these processes, that were named “pathologies”. Therefore, preventive measures have been proposed, and, in case of not being possible the use of these preventive measures, repairing measures also have been analysed. During the identification of the pathologies, they were classified into two different groups: (i) procedural instruction pathologies, in which the financial and economic imbalance hasn’t been identified and quantified; (ii) procedural execution pathologies, in which the financial and economic imbalance has already been identified and quantified. The reason of this classification is to identify the preventive and repairing measures easily. The majority of the preventive measures are contractual or regulatory. The main examples of contractual preventive measures are the discipline of the Dispute Board and the independent verifier, that can contribute to achieve technical pieces of information. An example of regulatory preventive measure is the due process of law. As the repairing measures, it was analysed the government financial guarantees to PFI projects, private mechanisms for solving disputes, and the judicial proceedings. It was identified that pathologies are not caused by statute issues (statute nº 8.666/93; 8.987/95; 11.079/04; 9.784/99), but by structuring concessions contracts and their regulation. Consequently, it is extremely important that public administration consider practical consequences of its own decisions to preserve stability at concessions contracts